Numerical Assessment of Total Nitrogen (Tn) Load Discharged from Rivers into Harima-Nada, the Seto Inland Sea, Using A Numerical Coupled Hydrological-Water Quality Model. Issue 1 (June 2021) - Pintos Andreoli, V; Mori, M; Koga, Y; Shimadera, H; Suzuki, M; Matsuo, T; Kondo, A
Abstract: Harima-Nada region, located in the east of Seto Inland Sea, is a semi-enclosed sea-area next to Osaka Bay that has been suffering a sustained oligotrophication process during the past 25 years. A hydrogeological model, coupled with a water quality model, was applied to assess the numerical discharge of freshwater and total nitrogen (TN) load from rivers into the sea. The model was validated for the main rivers from the northern and southern regions (the Kako River and the Yoshino River, respectively). The obtained results showed that the main contribution of freshwater and TN load to the sea comes from Hyogo Prefecture Rivers. The type of activities developed on each watershed showed to be substantially more relevant on TN load contribution than the size itself of the considered watershed. For the eight years considered in this study (2009 - 2016), the annual average of TN discharged into Harima-Nada was almost constant, while the volume of discharged freshwater showed more variations. Additionally, the sustained decrement in nitrogen concentration in Harima-Nada seemed not to be directly bonded with riverine TN load, suggesting that nitrogen availability is closely related to sea nutrients mechanisms more than to TN inland contribution.